PEMBERDAYAAN MASYARAKAT DUSUN KEPUH MULYODADI BAMBANGLIPURO BANTUL DALAM PEMBUATAN PRODUK SEDUHAN TANAMAN OBAT KELUARGA UNTUK HIPERKOLESTEROL - Yulianto, Danang; Wijaya, Andi; Yunita, Erma; Astuti, Harti (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2024)
Cholesterol is a molecule that is useful for the body to form hormones, vitamin D and other substances needed. Hypercholesterol conditions can cause cardiovascular disease because it has been shown to have a role in changing the structure of blood vessels so that it can interfere with endothelial function and cause lesions, plaques, occlusions, and emboli. This community service activity aims to increase community knowledge and skills regarding the processing of family medicinal plants that can be utilized for hypercholesterolemia. This community service activity was attended by 40 participants from Kepuh RT 2 Mulyodadi Village. The methods used in this service are direct and indirect methods, namely by lecturing cholesterol and traditional medicine ingredients used and direct practice of making anti-cholesterol teabags. The results of the implementation of community service activities regarding the utilization of Rosela flowers and Salam leaves as tea brewing products for hypercholesterolemia prevention therapy in Kepuh RT 2, Mulyodadi, Bambanglipuro, Bantul went well and received a positive response from residents. Counseling activities can increase knowledge and skills in processing medicinal plants into health drinks, especially for hypercholesterolemia.